Human capital and labor productivity in food industries of Iran - Afrooz, Ahmad; Abdul Rahim, Khalid; Mohd Noor, Zaleha; Lee, Chin (Canadian Center of Science and Education, 2010)
One of the most important factors that affect labour productivity is human capital. Due to the importance of Food Industries of Iran this paper examines the role of human capital on labour productivity in food industries of Iran over the 1995-2006 period. The study used the ratio of educated workers to total workers and the ratio of skilled workers to total workers as a proxy for human capital and applied the Cobb–Douglas production function of industry. The results showed that educated workers and skilled workers have a significant effect on labour productivity. The measurements of these effects were 0.14 and 0.42 for educated and skilled workers respectively. It can be concluded that education, skills and capital per worker (k=K/L) have a positive and significant effect on labour productivity in food industries of Iran.